Case Report: Complete Response of Recurrent and Metastatic Cystadenocarcinoma of the Parotid Gland With a Single Course of Combined Nivolumab and Ipilimumab Therapy - Nakamura, Yoshiyuki; Nakayama, Masahiro; Nishimura, Bungo; Okiyama, Naoko; Tanaka, Ryota; Ishitsuka, Yosuke; Matsumoto, Shin; Fujisawa, Yasuhiro (Frontiers in Oncology, 2021)
Although cystadenocarcinoma is classified as a low-grade histological subtype of salivary gland carcinoma (SGC), recurrence and metastases sometimes develop. However, standard treatments for advanced cases have not yet been established. Here, we present a case of unresectable local recurrence and cervical lymph node metastases of cystadenocarcinoma of the parotid gland with multiple lung nodules, all of which showed complete response with only a single course of combined nivolumab and ipilimumab therapy. The patient's medical history of metastatic melanoma roused our suspicions that the multiple lung nodules were cystadenocarcinoma metastases or malignant melanoma. Combination therapy was used based on our suspected diagnosis of lung metastases of melanoma although histological examination of the lung nodules could not be performed. While various chemotherapies are used for advanced SGCs including cystadenocarcinoma, overall, the results are unsatisfactory. In contrast, there have not yet been any reports of advanced cystadenocarcinoma of the salivary gland treated with immune checkpoint inhibitors (ICIs). Given that, in our case, a single course of combined ICI therapy induced a complete response in the unresectable and lymph node metastases from the cystadenocarcinoma and the multiple lung nodules, ICIs, including combined therapy, could be a promising treatment for advanced cystadenocarcinoma.